Regulation of viral and cellular promoter activity by polyomavirus early proteins. - Pannuti, A (1987)
The chloramphenicol-acetyl-transferase (CAT) expression system has been utilized to study the ability of the polyomavirus (Py) early proteins, the 100K large T, the 55K middle T and 22K small T-antigens, to activate a variety of eukaryotic promoters (the SV40 early, the alpha 2(1) collagen, the rabbit beta-globin, the polyomavirus early and the H-2 class I) in both transient and stable expression assays. We have found that either the complete polyomavirus early region or a plasmid expressing only the 55K middle T-antigen are capable of stimulating the expression of all the promoter-CAT plasmids in transient co-transfection experiments in both NIH-3T3 and Rat-2 cells. Conversely, the Py early proteins do not stimulate the transcription of most of the promoter-CAT genes stably introduced in the cell chromosomes, with the exception of H-2 class I promoter, when stimulation of transcription has been observed upon infection with recombinant retrovirus encoding the Py middle T-antigen.